2022
DOI: 10.2147/tcrm.s357214
|View full text |Cite
|
Sign up to set email alerts
|

The Role of D-Dimers in the Initial Evaluation of COVID-19

Abstract: Purpose The COVID-19 pandemic was noted for the high degree of contagion and the large number of cases, as well as for the various clinical forms, from asymptomatic towards rapid evolution to death. The hospitals limited care capacity imposed the need to identify some markers of unfavorable evolution. The purpose of our study is to identify the parameters correlated with COVID-19 unfavorable evolution and to draw the profile of the patient at risk of unfavorable evolution. This set of parameters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…[11] Intriguingly, elevated levels of DD were reported in severe COVID-19 illness compared to mild infection emphasizing its prognostic value in COVID-19 infection. [19] Parallel to CBC, an altered coagulation profile was observed between the 2 groups. Here, we found that elevated coagulation parameters are associated with poor prognosis, with an increase in PT (31.5%), PTT (10.5%), INR (26.3%), and DD (36.8%) among non-survivors.…”
Section: Discussionmentioning
confidence: 92%
“…[11] Intriguingly, elevated levels of DD were reported in severe COVID-19 illness compared to mild infection emphasizing its prognostic value in COVID-19 infection. [19] Parallel to CBC, an altered coagulation profile was observed between the 2 groups. Here, we found that elevated coagulation parameters are associated with poor prognosis, with an increase in PT (31.5%), PTT (10.5%), INR (26.3%), and DD (36.8%) among non-survivors.…”
Section: Discussionmentioning
confidence: 92%
“…Although subjects suffering from COVID-19 are at increased risk of thrombosis, and we have strong evidence that subjects with HHT often suffer from medical conditions that may negatively influence the clinical course of COVID-19 (like chronic anemia, heart failure, and pulmonary AVMs), recent data suggest that, actually, HHT patients may generally present milder forms of SARS-CoV2 infection [ 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Some preliminary data show a significant decrease in inflammatory cytokines detected in the HHT population—with differences lower than 50% for some cytokines like interleukines (ILs: IL-6, IL-1β, and IL12p40) and around 50% for Chemokine (C-C motif) ligand 20 (CCL20), Thrombospondin-1 (TSP-1), and Activin A [ 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. If confirmed by larger studies, these HHT characteristics may explain some sort of protection against developing severe forms of COVID-19 [ 70 , 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some preliminary data show a significant decrease in inflammatory cytokines detected in the HHT population—with differences lower than 50% for some cytokines like interleukines (ILs: IL-6, IL-1β, and IL12p40) and around 50% for Chemokine (C-C motif) ligand 20 (CCL20), Thrombospondin-1 (TSP-1), and Activin A [ 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. If confirmed by larger studies, these HHT characteristics may explain some sort of protection against developing severe forms of COVID-19 [ 70 , 71 , 72 , 73 ]. Our patient does not recall presenting with specific COVID-19 symptoms, but she opted for SARS-CoV2 vaccination in complete schedule as soon as it became available (March 2021).…”
Section: Discussionmentioning
confidence: 99%
“…I would like to applaud the authors on this original research into the role of D-dimers and other parameters that constitute the risk profile for severe COVID-19 evolution. 1 At this difficult time, research into the virus itself has been crucial in the effort to fight the global pandemic.…”
Section: Dear Editormentioning
confidence: 99%